Efficacy of gastric per-oral endoscopic myotomy remains similar after failure of interventional techniques in refractory gastroparesis - Chartier, Marion; Duboc, Henri; Moszkowicz, David; Dior, Marie; Le Gall, Maude; Coffin, Benoit; Soliman, Heithem (Clinics and research in hepatology and gastroenterology, 2024)
•What is already known on this subject?Gastric per-oral endoscopic myotomy (G-POEM) is a new therapeutic option in refractory gastroparesis.However, the efficacy of the procedure after previous interventional techniques has been poorly assessed.•What are the new findings?The efficacy rate of G-POEM in 32 patients previously treated by pyloric dilation and/or gastric electrical stimulation was similar to that in 16 patients naïve to instrumental technique (50.0% vs 56.3%; p=0.41).The complication rate was also similar.•How might it impact on clinical practice in the foreseeable future?G-POEM remains a safe and effective option even after the failure of previous instrumental procedures Gastric per-oral endoscopic myotomy (G-POEM) is a new therapeutic option for the treatment of refractory gastroparesis. However, the outcome of G-POEM after the failure of gastric electrical stimulation (GES) or other pylorus-targeting therapies has been poorly reported. Data were collected from patients referred for G-POEM for refractory gastroparesis. The efficacy in patients with previous interventional techniques was compared to patients naïve to instrumental technique. The primary endpoint was the 6-month clinical success rate, defined as at least a 1-point decrease in the Gastroparesis Cardinal Symptom Index (GCSI). Among 48 patients referred for G-POEM, 32 patients had previous instrumental treatments (66%): 15 (31%) had GES, and 17 (35%) had pyloric endoscopic dilation or toxin injection. The technical success rate was 100%. At 6 months, clinical success was achieved in 25/48 patients (52%) and the GCSI decreased from 3.38 (2.94–3.95) to 2.25 (1.11–3.36) (p < 0.001). The 6-month success rate was similar in patients with or without previous instrumental treatment (50.0% vs 56.3%; p = 0.41). The complication rate was also similar in the two groups (6.3% vs 12.5%; p = 0.59), with only one severe adverse event. The only predictive factor for success at 6 months was a higher body mass index (OR = 1.14 [1.01–1.32]; p = 0.05). G-POEM is safe and remains effective after GES or previous pyloric treatment failure, with 50% efficacy at 6 months. The therapeutic strategy in refractory gastroparesis remains to be defined.